2019
DOI: 10.1111/idj.12513
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and its related factors among Korean dentists: An online survey study

Abstract: Objectives The aims of this study were to investigate the dentists' job‐related stress using the newly developed Dentist Job Stress (DJS) questionnaire, and to explore the relationships among sociodemographic factors, job stress and mental health indicators, including psychosocial stress, depression, anxiety and sleep among Korean dentists. Materials and methods An online survey including 1,520 dentists was conducted using the Brief Encounter Psychological Instrument‐Korean version (BEPSI‐K), the Center for Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
2
17
0
1
Order By: Relevance
“…We found that the subjective psychological stress regarding 2019-nCoV infections was positively related to daytime dysfunction and total PSQI scores. These results were comparable to those reported previously for healthcare professionals in similar studies [ [15] , [16] , [17] ]. Psychological distress and concerns about the illness may be either a cause or a consequence of poor sleep or daytime dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the subjective psychological stress regarding 2019-nCoV infections was positively related to daytime dysfunction and total PSQI scores. These results were comparable to those reported previously for healthcare professionals in similar studies [ [15] , [16] , [17] ]. Psychological distress and concerns about the illness may be either a cause or a consequence of poor sleep or daytime dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…The lowest stress was observed for dentists with the highest income in the study. These findings are in line with the studies conducted on Romanian [ 27 ] and Korean dentists [ 23 , 28 ], where high income was found to have a negligible relationship with mental stress.…”
Section: Discussionsupporting
confidence: 92%
“… 46 In addition, a study on dentists found that job stress was associated with income. 47 Therefore, we encourage managers to provide good working conditions for workers and to find a balance between workers’ contributions and rewards by increasing workers’ compensation while they bring profits to the business. In addition, we recommend a number of additional physical activity interventions.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to job stress, studies have shown that effective organisational interventions, such as flexible working arrangements, improved communication and job redesign, can be an effective way to reduce stress in the workplace 46. In addition, a study on dentists found that job stress was associated with income 47. Therefore, we encourage managers to provide good working conditions for workers and to find a balance between workers’ contributions and rewards by increasing workers’ compensation while they bring profits to the business.…”
Section: Discussionmentioning
confidence: 99%